PERAN BAHASA ARAB SEBAGAI LINGUA FRANCA DALAM PENGUATAN PENDIDIKAN ISLAM DAN KOMUNIKASI ILMIAH - Nurhalim Nurhalim; Vivi Dwi Clarisa; Erlina Erlina; Koderi Koderi; Zainal Rafli; Tamer Sa'ad Ibrahim Al Khidr (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
Arabic holds a strategic position in the intellectual and spiritual history of Islam as the language of revelation as well as a medium for the transmission of knowledge across regions and generations. This study analyzes the role of Arabic as a lingua franca in Islamic education and contemporary scholarly communication through a qualitative-descriptive approach based on literature review. The results show that Arabic functions as an epistemological bridge between learners and the corpus of Islamic scholarship, and as a means of accessing classical texts and contemporary academic discourse. However, modern challenges such as globalization, the dominance of foreign languages, and insufficient academic proficiency in Arabic restrict the optimization of this role. The findings emphasize the need for strengthened language policies, curricular integration that combines textual literacy and scholarly communication, and the development of an academic culture rooted in Arabic. With these strategies, Arabic has the potential to be revitalized as a scientific lingua franca that strengthens the intellectual identity of Islam and enhances academic contribution at the global level.